Use of a specific set of learner-centered evidence-based teaching practices correlates with higher exam performance across seven STEM departments - Mallory A. Jackson; Hongjiao Liu; Sungmin Moon; Jennifer H. Doherty; Mary Pat Wenderoth (PLoS ONE, 2026)
Myriad studies support the claim that active learning improves student academic performance in STEM, yet lecture remains the dominant form of instruction. Many faculty offer multiple reasons for not using active learning with many expressing confusion as to what active learning is. In an effort to better understand how specific elements of active learning might contribute to enhanced academic performance, we used a more fine-grained classroom observation tool, PORTAAL, to observe teaching practices across 146 STEM courses. We used a principal component analysis to identify specific sets of teaching practices and we found a continuum of implementation of teaching practices that ranged from instruction-centered to learner-centered. The instruction-centered practices included high Bloom’s level questions, students working alone, instructors answering and explaining questions, and providing alternative answers. The learner-centered practices were volunteer or randomly-called students explaining answers, instructors prompting students’ logic, and instructors giving positive feedback. Using a linear mixed model to analyze the data from all courses, we found medium and medium-high levels of learner-centered teaching practices correlated with higher student exam performance compared to instruction-centered practices. We also analyzed interactions of both binary gender and first generation status with learner-centered teaching on exam scores. We propose that when instructors use these learner-centered practices, they shift the responsibility of the intellectual work of the problem—the learning—to the students. As even moderate levels of these learner-centered practices have a positive correlation with exam performance, faculty may incorporate these few key elements of learner-centered practices into their own teaching to enhance student learning.